2019
DOI: 10.1182/blood-2018-08-869057
|View full text |Cite
|
Sign up to set email alerts
|

Intrahepatic fibrin(ogen) deposition drives liver regeneration after partial hepatectomy in mice and humans

Abstract: K E Y P O I N T Sl Liver-associated tissue factor drives rapid intrahepatic coagulation after PHx.l Intrahepatic fibrin(ogen) deposition, but not thrombin-mediated platelet activation, promotes liver regeneration after PHx.Platelets play a pivotal role in stimulating liver regeneration after partial hepatectomy in rodents and humans. Liver regeneration in rodents is delayed when platelets are inhibited. However, the exact mechanisms whereby platelets accumulate and promote liver regeneration remain uncertain. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
55
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 49 publications
(67 reference statements)
6
55
0
Order By: Relevance
“…Increased intrahepatic fibrin(ogen) deposition is present in livers of patients after liver resection but absent in patients displaying postresection hepatic dysfunction. 112 Experimental and clinical studies support the importance of platelets on regeneration in cirrhosis. Pretreatment of cirrhotic rats with thrombopoietin prior to partial hepatectomy is associated with accumulation of platelets within the liver and correction of the impaired regeneration that is otherwise observed.…”
Section: Impaired Liver Regenerationmentioning
confidence: 96%
“…Increased intrahepatic fibrin(ogen) deposition is present in livers of patients after liver resection but absent in patients displaying postresection hepatic dysfunction. 112 Experimental and clinical studies support the importance of platelets on regeneration in cirrhosis. Pretreatment of cirrhotic rats with thrombopoietin prior to partial hepatectomy is associated with accumulation of platelets within the liver and correction of the impaired regeneration that is otherwise observed.…”
Section: Impaired Liver Regenerationmentioning
confidence: 96%
“…A recent elegant work indicates that fibrin contributes to liver regeneration by promoting intrahepatic platelet accumulation. 38 In this work, the authors showed that the tissue factor produced by hepatocytes after partial hepatectomy is critical for activating a coagulation cascade that leads to intrahepatic fibrin deposition and platelet accumulation in the remnant liver. Accordingly, thrombocytopenia was shown to impair hepatocyte proliferation in a surgical murine model of liver regeneration and many studies based on therapeutic enrichment of platelets during partial hepatectomy indicate pro-regenerating beneficial effects.…”
Section: Interaction Of Platelets With Liver Cells Platelets and Hepamentioning
confidence: 99%
“…1). As mentioned previously, hepatic platelet accumulation is very rapid after PHx, peaking within 30 minutes, 25,63 and platelet accumulation in the liver shortly after PHx is most impactful with respect to liver regeneration. Indeed, timing seems to be of critical relevance as platelet depletion prior to PHx significantly reduced hepatocyte proliferation, whereas antibody-mediated thrombocytopenia initiated 2 hours after PHx had a much less impact.…”
Section: Platelet Accumulation Within the Livermentioning
confidence: 53%
“…For example, we have shown that depletion of plasma fibrinogen with ancrod also prevented hepatic platelet accumulation. 63 This suggests that in addition to adhesive proteins such as VWF, coagulation factors are critical drivers of platelet accumulation in the liver after PHx, a potential basis for prior studies associating blood coagulation with liver regeneration. 63,64 Coagulation Factors in Liver Regeneration Activation of coagulation has been shown to promote liver regeneration.…”
Section: Platelet Accumulation Within the Livermentioning
confidence: 99%